Comportamiento organizacional y calidad de servicio administrativo según estudiantes de la carrera profesional de educación inicial facultad de ciencias de la educación y humanidades UNAP, Iquitos 2022 - Guerra Muñoz, Evelyn Alexandra (2024)
The purpose of the study was to explain the relationship that exists between organizational behavior and the quality of administrative service in students of the professional career of Initial Education, Faculty of Educational Sciences and Humanities UNAP 2022. Regarding the methodology; the type of research according to its descriptive scope and its quantitative approach, with a cross-sectional Correlational design, the technique used was the survey, the instruments for data collection were two questionnaires, with a population of 212 and a sample of 69 students from the first to fifth level of initial education. Obtaining as a result, with the Pearson correlation coefficient rxy= 0.532, indicates a moderate, direct and positive relationship between both variables. The study concluded that organizational behavior and administrative service quality are significantly related.